Participation of the Polish Parliament in the Execution of Judgments of the European Court of Human Rights* - Ciżyńska-Pałosz, Angelika (Teisė, 2022)
The main aim of this paper is to present the role of parliament in the process of implementation of European Court of Human Rights (ECHR) judgments in Poland. Firstly, the structure of the Polish parliament and the activity of two parliamentary committees dealing with the issue of the execution of ECHR judgments are presented. Then, the implementation by the Polish parliament of two basic tasks in this area is described: (1) participation in the enactment of laws aimed at removing regulations incompatible with the Convention from domestic law; (2) control of draft laws in terms of compliance with the Convention. Other activities undertaken by the Polish parliament to supervise the execution of judgments of the ECHR issued in cases against Poland are also shown. Finally, the actions taken by the Polish parliament are juxtaposed with the recommendations of the Council of Europe bodies. This allows the development of proposals to modify the Polish model and make it more effective in implementing the recommendations of the Council of Europe.